Ziziphus spina-christi as a natural feed supplement for sustainable livestock nutrition: An updated narrative review - Youssef A. Attia; Asmaa F. Khafaga; Ayman E. Taha; Islam M. Youssef; Khalid A. Asiry; Adel D. Al-Qurashi; Omer H.M. Ibrahim; Khaled H. El-Kholy; Rashed A. Alhotan; Salem R. Alyileili; Sara H.M. Hassab; Mohamed A. Al-Banoby; et al. (Livestock Science, 2026)

Electricity poverty in sub-Saharan Africa: Do green electricity generation and human development influence sustainable energy foreign direct investment in the long and short run? - Ahmed R. Rashed (The Social Science Journal, 2026)

Participatory Co-Design for Human–Elephant Coexistence: Integrating Local Knowledge into Early Warning System Planning in Odisha - Balu M. Menon; Tarek Rashed; Lekshmi Venkitesh P; Vasundharan Nidhi; Rao R. Bhavani (Environmental Management, 2026)

Combined Effects of Parasitic Infection and Heavy Metal Exposure on Health and Profitability of Cultured African Catfish (Clarias gariepinus) - Mahmoud Radwan; Mohammad R. K. Abdel-Samad; Aya Ramadan Rashed; Wafa Mohammed Al-Otaibi; Shahd Yassir; Moussa Attia Moussa (Biological Trace Element Research, 2025)

Neuroprotective Effects of Alpha-Lipoic Acid Against Behavioral Toxicity, Oxidative and Inflammatory Damage Caused by Titanium Dioxide Nanoparticles - Mahmoud A. Khedr; Sara E. El-Kazaz; Rashed R. Rashed; Hossam G. Tohamy; Mustafa Shukry; Amira A. Goma (Biological Trace Element Research, 2025)
Titanium dioxide nanoparticles (TiO₂-NPs) are used widely in various industries, but emerging evidence suggests their ability to elicit neurotoxicity. The present study evaluated the alpha-lipoic acid (ALA) neuroprotective potential against TiO₂-NP-induced cognitive and molecular impairments in male Sprague–Dawley rats. Twenty-four rats were allocated into four groups: negative control, TiO₂-NPs (150 mg/kg, i.p.), ALA (50 mg/kg, orally), and TiO₂-NPs + ALA. Treatments were administered on alternate days for 28 days. Neurobehavioral tests, including the open field test (OFT), elevated plus maze (EPM), novel object recognition test (NORT), and Morris water maze (MWM), revealed that TiO₂-NPs impaired memory and increased anxiety-like behavior, while ALA co-treatment significantly restored behavioral performance. TiO₂-NPs exposure significantly decreased antioxidant enzymes (SOD, CAT, GSH), increased lipid peroxidation (MDA), elevated proinflammatory cytokines (TNF-α, IL-6), and apoptotic marker (caspase-3), and reduced neurotransmitter levels (GABA and dopamine). ALA administration reversed these alterations, indicating antioxidant, anti-inflammatory, and neuroprotective effects. Gene expression analysis showed TiO₂-NPs upregulated BAX, NF-κB, APP, and MAPT and downregulated BCL-2 and Nrf2, consistent with neurodegenerative and apoptotic signaling. ALA co-treatment normalized these gene expressions. Histopathological analysis confirmed structural damage in the cerebrum and cerebellum after TiO₂-NPs exposure, which ALA markedly improved. These findings suggest that ALA offers significant neuroprotection against TiO₂-NP-induced toxicity via its antioxidant, anti-inflammation, and anti-apoptosis properties, and supports being a potential protective agent against nanoparticle-induced neurodegeneration.

Examining the Influence of Zinc Oxide Nanoparticles and Bulk Zinc Oxide on Rat Brain Functions: a Comprehensive Neurobehavioral, Antioxidant, Gene Expression, and Histopathological Investigation - Amira A. Goma; Alyaa R. Salama; Hossam G. Tohamy; Rashed R. Rashed; Mustafa Shukry; Sara E. El-Kazaz (Biological Trace Element Research, 2024)
The study aimed to assess the impact of zinc oxide nanoparticles (ZnONPs) on rats’ neurobehavior compared to bulk zinc oxide (BZnO). Thirty male Sprague-Dawley rats were randomly assigned to five groups. The control group received Tween 80 (10%), while the ZnONP groups were given ZnONPs at 5 and 10 mg/kg body weight dosages, and the bulk zinc oxide (BZnO) groups received BZnO at the same dosages. Behavioral observations, neurobehavioral examinations, and assessments of brain tissue oxidative markers, neurotransmitter levels, and histopathological changes were performed. The results indicated that ZnONP at a dosage of 5 mg/kg improved general behavior, locomotor activity, memory, and recognition and reduced fearfulness in rats. Conversely, the higher dosage of 10 mg/kg and the bulk form had adverse effects on general behavior, locomotor activity, and learning ability, with the bulk form demonstrating the most severe impact—znONP-5 treatment increased antioxidant enzyme levels and decreased inflammatory markers. BZnO-5 exhibited lower oxidative stress markers, although still higher than BZnO-10. Furthermore, ZnONP-5 and BZnO-5 increased neurotransmitter levels compared to higher dosages. ZnONP-5 upregulated the expression of brain-derived neurotrophic factor (BDNF) mRNA, while BZnO-5 showed increased BDNF mRNA expression and decreased expression of genes related to apoptosis and inflammation. In summary, ZnONPs at 5 mg/kg demonstrated positive effects on rat brain function and behavior, while higher dosages and the bulk form had detrimental effects. In conclusion, the studies emphasized the importance of further assessing various doses and forms of zinc oxide on brain health, highlighting the significance of dosage considerations when using nanomaterials.

Chamomile essential oil improves the growth, immunity, and antioxidant status of Nile tilapia exposed to nanosized alumina - Mayada R. Farag; Eman I. El Behery; Doaa S. Nouh; Youssef A. Attia; Rashed A. Alhotan; Mahmoud Alagawany; Alessandro Di Cerbo; Mona A Hassan (Aquaculture International, 2024)

Dietary flaxseed cake influences on performance, quality, and sensory attributes of eggs, serum, and egg trace minerals of laying hens - Youssef A. Attia; Ahmed A. Al-Sagan; El-Sayed O. S. Hussein; Marai J. Olal; Tarek A. Ebeid; Abdulaziz A. Al-Abdullatif; Rashed A. Alhotan; Salem R. Alyileili; Heba A. Shehata; Vincenzo Tufarelli (Tropical Animal Health and Production, 2024)

Pixel Reduction of High-Resolution Image Using Principal Component Analysis - Ramachandran Radhakrishnan; Manimegalai Thirunavukkarasu; R. Thandaiah Prabu; G. Ramkumar; S. Saravanakumar; Anitha Gopalan; V. Rama Lahari; B. Anusha; Shaik Hasane Ahammad; Ahmed Nabih Zaki Rashed; Md. Amzad Hossain (Journal of the Indian Society of Remote Sensing, 2024)

Protective influence of supplementary betaine against heat stress by regulating intestinal oxidative status and microbiota composition in broiler chickens - Ali R. Al Sulaiman; Ala M. Abudabos; Rashed A. Alhotan (International Journal of Biometeorology, 2024)

Yucca schidigera Extract Mitigates the Oxidative Damages, Inflammation, and Neurochemical Impairments in the Brains of Quails Exposed to Lead - Mayada R. Farag; Seham El-Kassas; Youssef A. Attia; Rashed A. Alhotan; Mohamed A. Mahmoud; Alessandro Di Cerbo; Mahmoud Alagawany (Biological Trace Element Research, 2024)

From source to house: unraveling the seasonal effect of water distribution system on drinking water quality of poultry farms under Egyptian environmental condition - Mohammed Abdelhameed Kamal; Rashed A. Alhotan; Ali R. Al Sulaiman; Elsayed Osman Hussein; Branislav Galik; Ahmed Ali Saleh (Environmental Science and Pollution Research, 2024)

Characterization and phylogenetic analysis of the complete mitochondrial genome of Mango tilapia (Sarotherodon galilaeus: Cichlidae) - Yosur G. Fiteha; M. A. Rashed; R. A. M. Ali; M. Magdy (Molecular Biology Reports, 2023)
Background Sarotherodon galilaeus (Linné, 1758) is a member of the family Cichlidae, which is considered the most important aquaculture freshwater species endemic to Africa and the Middle East. The genetics and molecular biology of this species are rare. This requires more comprehensive mitochondrial genomes-based phylogenetics to enhance understanding of the relationship and delineate this species. Methods and results Here, we assembled the complete mitogenome of S. galilaeus using Illumina high-throughput sequencing technology. The mango tilapia mitogenome was 16,631 bp in length with an AT composition of 53.4% and 46.4% GC content. It encodes 37 genes comprising two ribosomal RNA genes (rRNAs), 22 transfer RNA genes (tRNAs), and 13 protein-coding genes (PCGs) as well as the D-loop known as the control region. The phylogenetic tree was conducted to provide a relationship within the haplotilapiine lineage based on the maximum likelihood method, and the newly sequenced S. galilaeus was clustered with other Sarotherodon species. Conclusion Our results provide a new perception of the genetic basis of S . galilaeus species for further research on systematics, evolution, population genetics, and molecular ecology.

Mesenchymal Stem Cells and Selenium Nanoparticles Synergize with Low Dose of Gamma Radiation to Suppress Mammary Gland Carcinogenesis via Regulation of Tumor Microenvironment - Omayma A. R. Abozaid; Laila A. Rashed; Sawsan M. El-Sonbaty; Amira I. Abu-Elftouh; Esraa S. A. Ahmed (Biological Trace Element Research, 2023)
Breast cancer is one of the most prevalent and deadliest cancers among women in the world because of its aggressive behavior and inadequate response to conventional therapies. Mesenchymal stem cells (MSCs) combined with green nanomaterials could be an efficient tool in cell cancer therapy. This study examined the curative effects of bone marrow–derived mesenchymal stem cells (BM-MSCs) with selenium nanoparticles (SeNPs) coated with fermented soymilk and a low dose of gamma radiation (LDR) in DMBA-induced mammary gland carcinoma in female rats. DMBA-induced mammary gland carcinoma as marked by an elevation of mRNA level of cancer promoter genes (Serpin and MIF, LOX-1, and COL1A1) and serum level of VEGF, TNF-α, TGF-β, CA15-3, and caspase-3 with the reduction in mRNA level of suppressor gene (FST and ADRP). These deleterious effects were hampered after treatment with BM-MSCs (1 × 10 6 cells/rat) once and daily administration of SeNPs (20 mg/kg body weight) and exposure once to (0.25 Gy) LDR. Finally, MSCs, SeNPs, and LDR notably modulated the expression of multiple tumor promoters and suppressor genes playing a role in breast cancer induction and suppression.

Electrical characterization of phytoplankton suspensions using impedance spectroscopy - Margaret R. Jett; Mohamed Z. Rashed; Susan P. Hendricks; Stuart J. Williams (Journal of Applied Phycology, 2021)

Characterizing Zebra Chip Symptom Severity and Identifying Spectral Signatures Associated with ‘Candidatus Liberibacter solanacearum’-Infected Potato Tubers - Zhiguo Zhao; Sean M. Prager; Regina K. Cruzado; Xi Liang; William R. Cooper; Gongshe Hu; Arash Rashed (American Journal of Potato Research, 2018)

Petrology, geochemistry and remote sensing data of island arc assemblage along Wadi Abu Marawat, Central Eastern Desert, Egypt - A. M. Asran; R. Kh. Bekir; E. Abdel Rahman; A. Abdel El-Rashed (Arabian Journal of Geosciences, 2013)

Distribution and chemical fractionation of some heavy metals in bottom sediments of Lake Nasser - S. M. N. Moalla; R. M. Awadallah; M. N. Rashed; M. E. Soltan (Hydrobiologia, 1997)